(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2025)
Financial technology (FinTech) has revolutionized how individuals and businesses access financial services. By leveraging digital platforms, artificial intelligence (AI), and blockchain, FinTech has significantly enhanced financial inclusion, particularly in developing and emerging economies. This study explores how FinTech innovations bridge gaps in access to banking, payments, and credit, while also evaluating regulatory and cybersecurity challenges. Through a comparative analysis of international data (2019–2024), the paper identifies key success factors in FinTech ecosystems and policy frameworks fostering inclusive finance. The findings reveal that while FinTech has democratized financial access for millions globally, the uneven digital infrastructure and regulatory ambiguities continue to impede equitable growth.